Agri-business Incubation System in India: An Overview of ICAR - Saxena, Sanjeev; Datt, Shiv; Singh, Vikram (Indian Farming, 2020)
The approach of developing a culture of agribusiness incubation and agri-entrepreneurs is a prerequisite to accelerate the process to new technologies by the farmers’ for realizing the goal of doubling the farmers’ income by 2022. ICAR had taken the initiative to promote the IP and technology commercialization process, by institutionalization of the policy through development of guidelines and establishment of a suitable mechanism in three-tier mode in the ICAR institutes. Further, support is being given to the activities related to agri-business incubation which nurtures the technology entrepreneurs and starups in 50 ICAR Agri-business Incubation (ABI) centres network all over the country. These centres provide the effective platform for fostering the growth of sustainable business endeavour and provide the service support like research support, business planning, advice on management, marketing, technical and financial matters.